Doktrin Strict Liability sebagai Inclusive Mechanism Bagi Konsumen yang Dirugikan Akibat Ketidaksesuaian antara Produk dengan Gambar dalam Transaksi E-Commerce: Perspektif Hukum Inklusif: An Inclusive Legal Perspective - I Gede Yudi Mahendra; Kadek Januarsa Adi Sudharma; I Gede Agus Kurniawan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The rapid growth of e-commerce has created both opportunities and challenges in consumer protection, particularly in cases where products do not match the images displayed on digital platforms. This situation raises legal concerns because consumers often find themselves in a weak position to prove the fault of business actors. The prevailing paradigm of fault-based liability is considered less effective in ensuring access to justice, thereby necessitating a more inclusive legal mechanism. This study aims to analyze the liability of business actors within the framework of Indonesian positive law and to formulate the doctrine of strict liability as an inclusive legal mechanism in e-commerce transactions. The research employs a normative juridical method with both conceptual and statutory approaches. Data were collected through library research, which includes primary legal materials such as legislation, secondary materials in the form of scholarly literature, and tertiary materials that support legal interpretation.The findings indicate that although Law No. 8 of 1999 on Consumer Protection, the Indonesian Civil Code, and Law No. 11 of 2008 as amended by Law No. 19 of 2016 on Electronic Information and Transactions regulate the obligations of business actors, the fault-based paradigm still hinders consumers from obtaining effective protection. The novelty of this research lies in proposing the formulation of strict liability within an inclusive legal framework, where liability is automatically attached to business actors without requiring proof of fault. This concept is expected to strengthen consumer protection while ensuring a fair balance of interests in the digital trade ecosystem